2021
DOI: 10.3390/su13095181
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Tourism in Nitra, Slovakia: Overview of Current and Future Trends

Abstract: Cultural tourism has undergone fundamental changes in several countries of post-socialist Europe. In Slovakia, this fact concerns, for example, localities with a strong connection to the church and its cultural heritage. These monuments belong to the foundations of cultural tourism, yet the state intentionally did not prefer them as tourist destinations until 1989. Only after political and social changes were such localities exploited by tourism with a qualitative and quantitative increase in cultural tourism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Helping is an integral part of culture [45] and religion in Central Europe [46]. Experts and the general public are interested in why people behave either pro-socially or not in certain circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Helping is an integral part of culture [45] and religion in Central Europe [46]. Experts and the general public are interested in why people behave either pro-socially or not in certain circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that cultural tourism could be the primary driver of growth in rural areas as it yielded both economic and sociocultural benefits. Krogmann et al [57] characterised examples of localities with strong Church presence and its cultural heritage in Nitra, Slovakia. They demonstrated the cultural heritage potential of Nitra to be sufficient for the city to become an important cultural tourism hub in the region.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease is documented in Graph 2. It was caused mainly by the collapse of business tourism, trade fair tourism and congress tourism, which is considered to be the main generator of city traffic (Krogmann et al, 2021).…”
Section: [Insert Table 1 Here]mentioning
confidence: 99%